Physicochemical Stability of Reconstituted Decitabine (Dacogen®) Solutions and Ready-to-Administer Infusion Bags when Stored Refrigerated or Frozen - Kim Sun Hee; Heeb Rita Marina; Krämer Irene (De Gruyter, 2017)
Profound knowledge about the physicochemical stability is necessary in order to determine the "beyond-use-dates" of ready-to-administer preparations after reconstitution and dilution. This is especially true for unstable azanucleoside drugs like decitabine. The aim of this study was to determine the physicochemical stability of decitabine after reconstitution and dilution of Dacogen® 50 mg lyophilized powder. Decitabine concentration of Dacogen® powder reconstituted with cold water for injections (5 mg/mL) has been determined after storage in the original vials under refrigeration for 48 hours and in single use syringes in a freezer at -25 °C for 28 days. Concentration of diluted decitabine infusion solutions (0.5 mg/mL) prepared in prefilled 0.9 % NaCl polyolefine (PO) infusion bags has been determined after storage under refrigeration (2-8 °C) for 48 hours.